Analisis User Experience Aplikasi Siasat Mobile dengan Metode Heuristic Evaluation - Anugramidah Limbong Madika; Evangs Mailoa (STMIK Banjarbaru, 2023)
Siasat Mobile is an application used by students at Satya Wacana Christian University. Until now, there has been no research analyzing the level of user satisfaction and comfort with the Siasat Mobile application. Therefore, an analysis of the user experience of the Siasat Mobile application was conducted using the Heuristic Evaluation (HE) method. HE is a measurement method that covers user experience and comfort. HE includes 10 aspects of evaluation, including status visibility, suitability for daily life, user control, consistency, error handling, flexibility, and efficiency of use. This study resulted in a problem matrix experienced by users in the Siasat Mobile application, divided into two groups based on the urgency of the problems: major and minor, as well as recommendations for improving the interface according to user experience guidelines.Keywords: Siasat Mobile; User Experience; Heuristic Evaluation AbstrakSiasat Mobile merupakan salah satu aplikasi yang digunakan oleh mahasiswa di Universitas Kristen Satya Wacana. Hingga saat ini, belum ada penelitian yang menganalisa tingkat kepuasan dan kenyamanan pengguna pada aplikasi Siasat Mobile. Maka dari itu, dilakukan analisis pengalaman pengguna aplikasi Siasat Mobile menggunakan metode Heuristic Evalutation (HE). HE merupakan metode pengukuran yang mencakup pengalaman dan kenyamanan pengguna. HE mencakup 10 aspek peniliaian, termasuk visibilitas status, kesesuaian dengan kehidupan sehari-hari, kontrol pengguna, konsistensi, penanggulangan kesalahan, fleksibilitas, dan efisiensi penggunaan. Penelitian ini menghasilkan matriks permasalahan yang dialami pengguna pada aplikasi Siasat mobile yang dibagi ke dalam 2 kelompok berdasarkan urgensi permasalahan yaitu mayor dan minor serta rekomendasi perbaikan tampilan sesuai dengan user experience guidelines. Kata kunci: Siasat Mobile; User Experience; Heuristic Evaluation